Celecoxib vs diclofenac sodium in patients with knee osteoarthritis: A protocol for systematic review and meta analysis. Issue 15 (April 2020) - Huang, Hetao; Pan, Jianke; Yang, Weiyi; Chen, Hongyun; Liang, Guihong; Zeng, Lingfeng; Liu, Jun; Pan, Biqi
Abstract: Background: Knee osteoarthritis (KOA) is one of the most common chronic muscular diseases in old people. The purpose of this meta-analysis was to compare celecoxib and diclofenac sodium in patients with knee osteoarthritis (KOA). Methods: Randomized controlled trials (RCTs) and clinical controlled trials (CCTs) comparing the use of celecoxib and diclofenac sodium in KOA patients were retrieved from each database from the date of database inception to September 2019. The outcome measurements were the treatment effect, visual analog scale (VAS) score, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) level, and complication rate. The pooled data were evaluated with Review Manager 5.3.5. Results: The literature will provide a high-quality analysis of the current evidence supporting celecoxib for KOA based on various comprehensive assessments including the treatment effect, visual analog scale (VAS) score, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) level, and complication rate. Conclusion: This proposed systematic review will provide up-to-date evidence to assess the effect of celecoxib in the treatment for patients with KOA. Research Registry registration number: reviewregistry827. Abstract : Supplemental Digital Content is available in the text